A new volumetric geometric model for cutting procedures in surgical simulation. (September 2019) - Shi, Wen; Liu, Peter Xiaoping; Zheng, Minhua
Abstract : highlights: A new cutting concept was proposed for surgical simulation. A novel volumetric geometric model based on volume rendering and Bézier curve, is presented for cutting procedures. The edges of the incisions optimized by the proposed geometric model are smooth and the details of internal structures of soft tissues are clearly rendered. The cutting effects of different types of virtual organs are properly simulated. The computational efficiency is improved by octree and compact bounding box. Abstract: Background and objectives: Cutting procedures are the most common operations in surgical simulation. In order to provide realistic visual feedback with the details of the internal structures of soft tissue to the operator, a novel volumetric geometric model is presented for cutting procedures in surgical simulation. Methods: A novel volumetric geometric model, which is based on volume rendering and the Bézier curve, is presented for cutting procedures. The Bézier curve is used to optimize the physical model of cutting simulation, making the edge of incision smooth without increasing the computational load of the physical model. Volume rendering is used to render the cutting process, which improves significantly the realism of simulation since both surface textures and the details of the internal structures of soft tissues are rendered. Results and Conclusions: The simulation results show that the edges of the incision optimized by using the proposed geometric model are smooth and the details of internal structures of soft tissue can be rendered. In comparison with other volumetric models, the computational efficiency is much improved. Compared with conventional cutting simulation methods, the proposed volumetric geometric model improves the effects of visual feedback since both surface and internal structures are rendered according to the optimized physical model.